Evaluation of viscosity and thermal conductivity of graphene nanoplatelets nanofluids through a combined experimental–statistical approach using respond surface methodology method. (December 2016) - Iranmanesh, Soudeh; Mehrali, Mohammad; Sadeghinezhad, Emad; Ang, Bee Chin; Ong, Hwai Chyuan; Esmaeilzadeh, Alireza
Abstract: In the present study, three influential parameters including concentration, temperature and specific surface area of graphene nanosheets were investigated, which are the effective parameters on the viscosity and thermal conductivity of aqueous graphene nanosheets (GNP) nanofluids. A mathematical model developed by respond surface methodology (RSM) based on a central composite design (CCD). Also, the significance of the models was tested using the analysis of variance (ANOVA). The optimum results of aqueous GNP nanofluid showed that the concentration has a direct effect on the relative viscosity and thermal conductivity. Furthermore, predicted responses proposed by the Design Expert software were compared with the experimental results. The statistical analysis of the predicted values was in satisfactory agreement with the empirical data.